Capitalism's Handmaidens - Langworthy, Melissa (Edinburgh University Press, 2026)
When we think of a “woman entrepreneur”, what comes to mind? Women entrepreneurs hold a dominant presence in political, social, economic and development imaginaries, as a global class of workers typifying the contemporary, neoliberal era. Their enterprise is readily proffered as the evidence of a nation’s progress, inclusion and development. International institutions, development banks, states, civil society groups, corporations and international financial institutions promote women’s enterprise in nearly every corner of the globe. A powerful mythology has grown up around the idea of women as empowered, financial saviour-mothers who benefit the prosperity, inclusivity, and security of a nation and the global economy. In this book, Melissa Langworthy exposes these myths for what they are and in offering a political economy of women’s enterprise, she asks what value women’s enterprise gives, not to women, but to the institutions that have shaped them and placed them in the centre of the global imaginary.